(untitled) (Indian Journal of Animal Production and Management, 2024)
A total of 60 day old sexed-female Vanaraja chicks were reared for 0-34 weeks of age. Birds were divided randomly into three dietary treatments composed of 20 birds per group with 5 replicates each. The experimental treatments were fed: basal diet T1, 2.5g of cinnamaldehyde T2, and 5g of cinnamaldehyde T3 per kg feed. The blood sample was taken on the 4th and 8th month to examine haematological and biochemical parameters. At the end of the experimental trial, it has been observed that chicken fed with cinnamaldehyde had a lower level of haemoglobin, Packed cell volume, cholesterol, Low Density Lipoprotein, triglyceride, and glucose. However, there was no significant difference in High Density Lipoprotein among the treatment groups. In conclusion, using cinnamaldehyde as a dietary supplement helps in the reduction of certain blood constituents of Vanaraja birds.